# (5a^3b^4)^2=?

*I don't get this one...PLease Help!

(5a3b4)2=

(5)2*(a3)32*(b4)2=

25*a6b8

I hope this turns out right. With all of these exponents it is easy to forget to turn them off and or to put parentheses in the wrong place.

thanks once again...do you think you can help me with this one:
(-mn^8)^3
*Would this one be:-m^3n^24?

The middle step is not correct. Strike the 3 but leave everything else.

That is correct. Be sure and read my correction post for the first one.

(-2x^2y)^3*(5xy^3)^2
*I reallllllyyyyy need help with this one...

## To simplify the expression (-2x^2y)^3*(5xy^3)^2, we need to expand the powers and then multiply the terms.

Let's start with the first part (-2x^2y)^3. To raise a power to another power, we multiply the exponents. So we have:
(-2x^2y)^3 = -2^3 * (x^2)^3 * y^3

Simplifying further, we get:
(-2)^3 = -8
(x^2)^3 = x^(2*3) = x^6
y^3 remains the same.

So the first part becomes: -8x^6y^3

Moving on to the second part (5xy^3)^2, we have:
(5xy^3)^2 = 5^2 * (x)^2 * (y^3)^2

Simplifying further, we get:
5^2 = 25
x^2 remains the same
(y^3)^2 = y^(3*2) = y^6

So the second part becomes: 25x^2y^6

Now, we multiply the two parts together:
(-8x^6y^3) * (25x^2y^6) = -8 * 25 * x^6 * x^2 * y^3 * y^6

Simplifying further:
-8 * 25 = -200
x^6 * x^2 = x^(6+2) = x^8
y^3 * y^6 = y^(3+6) = y^9

So the final answer is: -200x^8y^9.